On the Identity of Barleria terminalis Nees - Malhotra, S. K.; Moorthy, S. (Indian Forester, 1981)
A critical study of Barleria strigosa Willd. Var. terminals (Nees) C.B. Charke reveals Nees was fully justified in treating B. terminalis as a distinct species distinguished from each other by many charaters. Unlike B. strigosa Willd., which is mostly distributed throughout India except along the Western ghats, B. terminalis Nees is so far known to be confined only along the Western ghats.